Counter-storytelling: The Experiences of Women of Colour in Higher Education - Verjee, Begum (Atlantis)

(untitled) (Mount Saint Vincent University, 2013)
This article is based on a research study that explored the experiences of women of colour at the University of British Columbia (UBC), using critical race feminism as epistemology. Critical race feminism sets out to understand how society organizes itself along the intersections of race, gender, class, and all forms of social hierarchies. Critical race feminist theory utilizes counter-storytelling to legitimize the voices and experiences of women of colour, and draws on these knowledges in efforts to eradicate all forms of social oppression. In this research study, women of colour students, non-academic staff, faculty, and non-university community members shared their experiences of systemic exclusion at and in relation to UBC. These stories, based on intersectional and multiple sites of op-pression, unveiled hegemonic structures and practices which prevented these groups from participating as legitimate, equal, and contributing members of the institution.